Competition between Nucleophilic Substitution of Halogen (SNAr) versus Substitution of Hydrogen (SNArH)—A Mass Spectrometry and Computational Study. Issue 16 (12th March 2015) - Błaziak, Kacper; Mąkosza, Mieczysław; Danikiewicz, Witold
Abstract The mechanism of intramolecular gas‐phase reactions of N‐(2‐X‐5‐nitrophenyl)‐N‐methylacetamide carbanions (X=H, F, Cl) has been studied using negative ion electrospray mass spectrometry ((−)ESI‐MS) technique and modelled computationally. It was proven that all three anions form cyclic σH adducts, which undergo elimination of water. In the case of X=F, formation of the σF adduct, leading to SNAr reaction, was a competing process. This is the first proof that also in the gas phase formation of σH adduct proceeds faster than σX adduct and only when X=F, rates of these two processes are comparable. The experimental results are in full agreement with quantum chemical calculations.